2016
DOI: 10.1007/s11356-016-6631-3
|View full text |Cite
|
Sign up to set email alerts
|

Co and Fe-catalysts supported on sepiolite: effects of preparation conditions on their catalytic behaviors in high temperature gas flow treatment of dye

Abstract: An efficient adsorbent/catalyst Co and Fe-catalysts loaded on sepiolite (Co-Fe/sepiolite) was successfully prepared for high temperature gas flow catalytic reaction by a simple impregnation method. The impact of preparation conditions (such as pH value of impregnation solution, impregnation time, calcination temperature, and time) on catalytic activity was studied. We found that the catalytic activity of Co-Fe/sepiolite was strongly influenced by all the investigated parameters. The regeneration efficiency (RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…In addition, the kinetics of the catalytic degradation of methylene blue over NiO/sepiolite is discussed. The regeneration temperature for the NiO/sepiolite materials was much lower than in our previous work 19 .…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In addition, the kinetics of the catalytic degradation of methylene blue over NiO/sepiolite is discussed. The regeneration temperature for the NiO/sepiolite materials was much lower than in our previous work 19 .…”
Section: Introductioncontrasting
confidence: 53%
“…In this study, it is shown that high-temperature gas flow regeneration processes are a promising option, since they are fast processes that are performed in situ within the adsorption column under ambient conditions and at lower temperatures. Our previous report demonstrated that high-temperature gas flow regeneration was an effective process 19 . This technique includes adsorption and high-temperature gas flow regeneration that takes place within a single unit.…”
Section: Introductionmentioning
confidence: 99%
“…22 Our previous work has highlighted the efficiency of the adsorption and hot gas stream regeneration process for dye wastewater treatment. 12,23,24 This gas–solid catalytic reaction refers to a cycle of dye adsorption from aqueous solutions and hot O 2 gas stream regeneration. The regeneration rate of Co–Fe/sepiolite can reach 85.7% at 650 °C within 10 minutes.…”
Section: Introductionmentioning
confidence: 99%